Heterophil/Lymphocyte Ratio Level Modulates Salmonella Resistance, Cecal Microbiota Composition and Functional Capacity in Infected Chicken - Thiam, Mamadou; Wang, Qiao; Barreto Sánchez, Astrid Lissette; Zhang, Jin; Ding, Jiqiang; Wang, Hailong; Zhang, Qi; Zhang, Na; Wang, Jie; Li, Qinghe; Wen, Jie; Zhao, Guiping (Frontiers in Immunology, 2022)
The gastrointestinal microbiota plays a vital role in ensuring the maintenance of host health through interactions with the immune system. The Heterophil/Lymphocyte (H/L) ratio reflects poultry’s robustness and immune system status. Chickens with low H/L ratio are superior to the chickens with high H/L ratio in survival, immune response, and resistance to Salmonella infection, but the underlying mechanisms remain unclear. This study aimed to identify microorganisms associated with resistance to Salmonella Enteritidis infection in chickens based on the H/L ratio. The 16S rRNA and metagenomic analysis were conducted to examine microbiome and functional capacity between the 2 groups, and Short Chain Fatty Acids (SCFAs) and histopathology were conducted to explore the potential difference between susceptible and resistant groups at 7 and 21 days post-infection (dpi). The microbiome exploration revealed that low H/L ratio chickens, compared to high H/L ratio chickens, displayed a significantly higher abundance of Proteobacteria (Escherichia coli) and Bacteroidetes (Bacteroides plebeius) at 7 and 21 dpi, respectively. Anaerostipes (r = 0.63) and Lachnoclostridium (r = 0.63) were identified as bacterial genus significantly correlated with H/L (P < 0.001). Interestingly, Bacteroides was significantly and positively correlated with bodyweight post-infection (r = 0.72), propionate (r = 0.78) and valerate (r = 0.82) contents, while Salmonella was significantly and negatively correlated with bodyweight post-infection (r = − 0.67), propionate (r = − 0.61) and valerate (r = − 0.65) contents (P < 0.001). Furthermore, the comparative analysis of the functional capacity of cecal microbiota of the chickens with high and low H/L ratio revealed that the chickens with low H/L ratio possess more enriched immune pathways, lower antibiotic resistance genes, and virulence factors compared to the chickens with high H/L ratio. These results suggest that the chickens with low H/L ratio are more resistant to Salmonella Enteritidis, and it is possible that the commensal Proteobacteria and Bacteroidetes are involved in this resistance against Salmonella infection. These findings provide valuable resources for selecting and breeding disease-resistant chickens.